Growth of Krey Payung (Filicium decipiens) on Medium of Ex Sand Mine with the Addition of Charcoal and NPK Fertilizer - Basuki Wasis; Nuri Jelma Megawati (Jurnal Silvikultur Tropika, 2013)
Mining activity is an exploitation of natural resources, such as land clearing, extraction, digging and landfilling. One of mining activities that often done by people is sand mining. Some problems occur by sand mining, i.e. landslide, sedimentation, flood, the loss of soil organic matter, the loss of soil horizon, soil structure changes, air pollution in the form of dust particle and destruction of accessibility. Revegetation must be conducted on ex mined land, but it has some constraints, such as domination of sand texture, low CEC and low soil nutrient. Application of charcoal and NPK fertilizer are expected to overcome those problems. Krey payung has good adaptability in various soil types, producing a lot of litters for soil repairment, has a good crown to cover the soil and has attractive performance. The result showed that combination of charcoal without NPK fertilizer gave the best growth for krey payung seedling. The largest single charcoal application, i.e. 10 % in soil planting medium of ex sand mine gave the best growth for Krey payung seedling. Medium without NPK fertilizer gave the best response for krey payung seedling growth. The addition of NPK on soil medium of ex sand mining did not give good response for the growth of krey paying seedling.Key words: charcoal, krey payung, NPK fertilizer, sand mine